Mechanism Analysis of the Influence of Delay Period on Mechanical Properties of Reactive Powder Concrete - Wang, Xiaohui; Zhao, Qingxin; He, Xiaojun; Zhang, Shuang (Frontiers in Materials, 2021)
In order to analyze the influence mechanism of delay period on the mechanical properties of reactive powder concrete (RPC), the compressive strength of RPC with delay periods of 18 h, 24 h and 30 h was tested at the age of 7 d, 28 d and 90 d respectively. The maximum compressive strength of 7 d and 28 d was taken as the reference value, and the compressive strength of 90 d was compared with it to calculate the long-term reduction rate. The results showed that compared with the RPC with delay period of 18 h, the compressive strength of the RPC with delay periods of 24 h and 30 h increased by 3.2% and 4.2% respectively, and the long-term strength reduction ratio decreased by 22.8% and 71.9% respectively. The constitutive model curves of RPC under different delay period showed that the initial elastic modulus E increased with the delay period and the strength and rigidity of RPC increased with the extension of delay period. According to the non-evaporation water quantity test, it could be speculated that the quantities of hydration products of the RPC with delay periods of 24 h and 30 h slightly increased compared with the RPC with delay period of 18 h. X-ray diffraction (XRD) analysis showed that the delay periods of 24 h and 30 h consumed more 3CaO·SiO2 (C3S) and 2CaO·SiO2 (C2S) compared with delay period of 18 h. Seen from the scanning electron microscope (SEM) image, the structures of the three groups of samples were relatively dense and had no significant difference. Through energy dispersive X-ray spectroscopy (EDS) analysis, the calcium-silicon ratio of hydration products of the RPC with delay periods of 18 h, 24 h and 30 h was 1.81, 1.56 and 1.54 respectively. An appropriate delay period (30 h in this paper) made the system generate more hydration products, then improved the compactness of the internal structure and reduced the calcium-silicon ratio of hydration products, and it was conducive to the growth of RPC compressive strength and the stability of long-term compressive strength.